Rehabilitation outcomes and parameters of blood flow restriction training in ACL injury: a scoping review - Caetano, Daniel (2022)
To identify the outcomes of physical function, physical fitness, training, and cuff parameters, used in BFRT in ACL rehabilitation. This scoping review was initiated on April 25th, 2020, according to the PRISMA Extension for Scoping Reviews (PRISMA-ScR). Relevant literature was identified searching three main concepts: BFRT, rehabilitation and ACL injury on MEDLINE (PubMed), CENTRAL of Cochrane Library, Web of Science and PEDro. Studies looking at adults with a primary ACL injury undergoing conservative or pre/post-surgery rehabilitation with BFR or BFRT, with physical fitness and physical function as outcomes or other physical outcomes were included. Sixty-eight articles were identified and six were included. One article was added through backward tracking. All studies used BFRT in the ACL injury surgical rehabilitation. Most studies evaluated physical fitness (muscular strength and volume) however, physical function was not considered a pri mary outcome. Training and cuff parameters were heterogeneously prescribed. The existing evidence is not enough to draw definitive conclusions due to the heterogenous reported outcomes and parameters. Future investigation with standardized outcome measures and specific protocols are needed to draw conclusions on patients’ physical function, so BFRT can be used more effectively in clinical rehabilitation practice.